Status of metabolic profiles during anorexia and sub-clinical ketosis of bovines - KUMAR, RAKESH; SHARMA, I J; QUADRI, M A; RAO, M L V (The Indian Journal of Animal Sciences, 2014)
In the blood of 72 anorexic and sub-clinically ketotic bovines the metabolic profiles of carbohydrate and lipid were worked out. The energy producing substrates such as blood glucose, oxaloacetate, plasma total volatile fatty acids were deficient and the pyruvate, lactate, free fatty acids, cholesterol and ketone bodies got elevated in anorexic and sub-clinical ketotic bovines, particularly around two months postpartum. The deficient energy supply subsequently caused the fall in milk production of these animals.